Rasskaz otca - Andrey Filchenko; Julia Kurganskaja; Olga Potanina; Petro Milimov; Sergej Kovylin (Andrey Filchenko, 2012)
Eastern Khanty Comprehensive Documentation & Analysis of two Endangered Siberian Languages: legacy data and last speakers of Eastern Khanty and Southern Selkup